In vivo and in silico studies of the effects of oil extracted from Cannabis sativa L. seeds on healing of burned skin wounds in rats - Bouarfa, Mouna; Chebaibi, Mohamed; Ez-Zahra Amrati, Fatima; Souirti, Zouhair; Saghrouchni, Hamza; El atki, Yassine; Bekkouche, Khalid; Mourabiti, Hajar; Bari, Amina; Giesy, John P.; Mohany, Mohamed; Al-Rejaie, Salim S.; et al. (Frontiers in Chemistry, 2024)
Introduction This study investigates the potential effects of cannabis seed oil (CSO) on the wound healing process. The aim was to assess the efficacy of CSO in treating skin wounds using an animal model and to explore its anti-inflammatory properties through in silico analysis. Methods Eighteen male albino Wistar rats, weighing between 200 and 250 g, were divided into three groups: an untreated negative control group, a group treated with the reference drug silver sulfadiazine (SSD) (0.01 g/mL), and a group treated topically with CSO (0.962 g/mL). The initial wound diameter for all groups was 1 cm. In silico studies were conducted using Maestro 11.5 to evaluate the anti-inflammatory effects of phytoconstituents against cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2). Results CSO and SSD treatments led to a significant reduction (p <0.05) in the size of burned skin wounds by day 5, with contraction rates of 53.95% and 45.94%, respectively, compared to the untreated negative control group. By day 15, wounds treated with CSO and SSD had nearly healed, showing contraction rates of 98.8% and 98.15%, respectively. By day 20, the wounds treated with CSO had fully healed (100%), while those treated with SSD had almost completely healed, with a contraction rate of 98.97%. Histological examination revealed granulated tissue, neo-blood vessels, fibroblasts, and collagen fibers in wounds treated with CSO. In silico studies identified arachidic acid, γ-linolenic acid, and linolenic acid as potent inhibitors of COX-1 and COX-2. Serum biochemical parameters indicated no significant changes (p > 0.05) in liver and kidney function in rats treated with CSO, whereas a significant increase (p < 0.01) in ALAT level was observed in rats treated with SSD. Discussion The findings demonstrate that CSO has a promising effect on wound healing. The CSO treatment resulted in significant wound contraction and histological improvements, with no adverse effects on liver and kidney function.However, the study's limitations, including the small sample size and the need for detailed elucidation of CSO's mechanism of action, suggest that further research is necessary. Future studies should focus on exploring the molecular pathways and signaling processes involved in CSO’s pharmacological effects.